Non-Alcoholic Fatty Liver Disease and Metabolic Syndrome: Diagnostic and Laboratory Approach - Victoria Indah Mayasari; Yessy Puspitasari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Both Non-Alcoholic Fatty Liver Disease (NAFLD) and metabolic syndrome are health problems worldwide. Various studies suggest that NAFLD and metabolic syndrome have a two-way relationship. Metabolic syndrome can be preceded by NAFLD and NAFLD can be a manifestation of the metabolic syndrome. Because of the relationship between the two, the diagnosis and management of NAFLD and metabolic syndrome are important to prevent complications such as cardiovascular disease, liver cirrhosis, and malignancy. The diagnosis of metabolic syndrome can be made based on various diagnostic criteria determined by several health organizations, such as WHO, IDF, and NCEP-ATP. Since NAFLD is asymptomatic until advanced disease, many patients are only identified at advanced stages. Liver biopsy is currently the gold standard for diagnosing NASH, which is a type of NAFLD. This procedure is invasive, and many studies are currently looking for and assessing non-invasive markers for NAFLD and metabolic syndrome. Laboratory as diagnostic support plays an important role in the diagnosis of NAFLD and metabolic syndrome. Non-invasive laboratory tests with high sensitivity and specificity are expected to contribute to the early diagnosis of NAFLD and metabolic syndrome. Various laboratory parameters have been developed to support the diagnosis of NAFLD and metabolic syndrome.